Hebb's Neural Networks Support the Integration of Psychological Science. - Posner, Michael I.; Rothbart, Mary K. (Canadian Psychology, 2004)
In a recent paper and forthcoming volume, the former President of the American Psychological Association, Robert Sternberg, calls for an effort to reintegrate psychological science (Sternberg, in press; Sternberg & Grigorenko, 2001). In this paper we argue that D. O. Hebb, beginning with his technical volume in 1949 and continuing through a series of introductory textbooks, has convincingly presented the basis for such integration. The basis for this integration lies in understanding how genes and experience shape neural networks underlying human thoughts, feelings, and actions. Why has not Hebb's accomplishment been generally recognized as providing the needed integration for psychology? We suggest that the methods available to Hebb, mostly animal research and behavioural human experiments, were not sufficient to provide empirical methods for linking his conceptual nervous system to real events in the human brain. This methodology has now been provided by neuroimaging. While Hebb also recognized the importance of studying individual differences in intelligence and affect, there were also no methods for exploring the specific genes that were an important source of these differences. The human genome project has provided new methods for exploring this issue. Hebb's basic idea, together with the new methodological tools and new disciplines (e.g., cognitive, affective, and social neuroscience), all based on network views, give abundant evidence of the value of employing the converging operations strategy advocated by Sternberg and Grigorenko (2001). It is important that psychology recognize the need for integrating cognitive, affective and, social neuroscience with psychology, because many of the theoretical questions that need to be addressed by neuroimaging and genetic studies are exactly those that a century of psychologists have explored. The neuroscience approach provides crucial constraints for psychological theories, but also benefits from a closer connection with the psychological level of analysis. Dans un article paru récemment et dans un ouvrage à paraître, l'ancien président de l'American Psychological Association, Robert Sternberg, fait valoir la nécessité de déployer les efforts nécessaires pour réintégrer la psychologie en tant que science (Sternberg, sous presse; Sternberg & Grigorenko, 2001). Dans le présent article, nous soutenons que D. O. Hebb a, en publiant son volume technique en 1949 et, par la suite, une série de manuels d'introduction, présenté de manière convaincante la base d'une telle intégration. Le fondement de cette intégration repose sur la compréhension du rôle des gènes et de l'expérience dans le fąconnement du réseau neuronal sousjacent de la pensée, des sentiments et des gestes chez l'être humain. Pourquoi ne reconnaît-on pas d'emblée le rôle des réalisations de D. O. Hebb dans cette intégration si nécessaire à la psychologie? Nous avan̨cons que les méthodes dont disposait Hebb — des activités de recherche sur les animaux et des expériences sur le comportement humain pour la plupart — n'étaient pas suffisantes pour produire des méthodes empiriques qui auraient pu relier son système nerveux conceptuel à des activités réelles du cerveau humain. Cette méthodologie est aujourd'hui appuyée par la neuroimagerie. Bien que Hebb ait lui aussi reconnu l'importance d'étudier les différences individuelles qui caractérisent l'intelligence et l'affect, il n'existait, à son époque, aucune méthode permettant d'étudier à fond les gènes qui étaient à l'origine de ces différences. Le projet du génome humain a fourni des nouvelles méthodes d'analyse de cette question. L'idée fondamentale chez Hebb, de même que les nouveaux outils méthodologiques et les nouvelles disciplines (p. ex., la neuroscience cognitive, affective et sociale) qui se fondent toutes sur le réseau neuronal, fournit des preuves abondantes de la valeur du recours à la stratégie des opérations convergentes mise de l'avant par Sternberg et Grigorenko (2001). Il importe que la psychologie reconnaisse la nécessité d'intégrer la neuroscience cognitive, affective et sociale avec la psychologie, car plusieurs des questions théoriques que doivent aborder la neuroimagerie et la génétique sont en tout point les mêmes que celles que se posaient, il y a un siècle, les psychologues. L'approche de la neuroscience fournit des contraintes critiques qui alimentent les théories psychologiques mais elle offre aussi un contact plus étroit avec le niveau d'analyse de la psychologie. Reprinted by permission of the publisher.